Diagnostics of a Clamping Joint System - Musil Miloš; Úradníček Juraj; Páleník Marek; Chlebo Ondrej (Journal of Mechanical Engineering, 2022)
The article describes a diagnostic method, on the basis of which it is possible to assess whether there is a loose connection in the clamping system (detection) and to determine which of them is loose (localization). The diagnostic method is based on comparing the drops in the natural frequencies of a measured system with respect to a reference system, which simulates the desired state. When analysing the drop in natural frequencies in order to locate the loosening, it is necessary to relate this drop to the position of the clamping joints within the considered mode shape.